2018
DOI: 10.3390/medicines5030068
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Notch Signaling and Leptin-Notch Crosstalk in Pancreatic Cancer

Abstract: There is accumulating evidence that deregulated Notch signaling affects cancer development, and specifically pancreatic cancer (PC) progression. Notch canonical and non-canonical signaling has diverse impact on PC. Moreover, the actions of RBP-Jk (nuclear partner of activated Notch) independent of Notch signaling pathway seem to affect differently cancer progression. Recent data show that in PC and other cancer types the adipokine leptin can modulate Notch/RBP-Jk signaling, thereby, linking the pandemic obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 108 publications
0
13
0
Order By: Relevance
“…Thus, several data strongly support the involvement of leptin in common endocrine related cancer in women [ 161 ], especially, breast cancer [ 145 , 162 , 163 ]. Additionally, leptin have been suggested as part of the mechanisms involved in the development of obesity-related carcinogenesis in pancreatic [ 164 ], prostate [ 165 ] and colorectal cancer [ 166 ].…”
Section: Leptin As a Mediator Of Inflammationmentioning
confidence: 99%
“…Thus, several data strongly support the involvement of leptin in common endocrine related cancer in women [ 161 ], especially, breast cancer [ 145 , 162 , 163 ]. Additionally, leptin have been suggested as part of the mechanisms involved in the development of obesity-related carcinogenesis in pancreatic [ 164 ], prostate [ 165 ] and colorectal cancer [ 166 ].…”
Section: Leptin As a Mediator Of Inflammationmentioning
confidence: 99%
“…Researchers have revealed that Notch signaling pathway plays a critical effect on tumor formation and progression 11–14 . Moreover, studies have found that activation of the Notch signaling pathway can promote tumor cell proliferation, which is related to the occurrence of many solid tumors, such as breast cancer and pancreatic cancer 15,16 . In summary, this study aim to reveal whether MEHP exposure can affect the proliferation of NB by regulating the Notch signaling pathway.…”
Section: Introductionmentioning
confidence: 94%
“…The combination of gemcitabine and Notch-targeting agents has been abundantly studied in pancreatic cancer. Different Notch receptors and ligands contribute to EMT, CSC maintenance, stroma-induced resistance, and to the crosstalk with survival pathways such as NF-κB and PI3K/AKT, favoring the survival of resistant pancreatic clones [570]. Reasonably, combinations of different GSI and Notch-targeting antibodies affected various mechanisms of gemcitabine resistance and improved its anti-viability effects in in vitro experiments.…”
Section: Gemcitabinementioning
confidence: 99%